Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan Melalui Perilaku Kreatif Pemimpin Sebagai Variabel Intervening (Studi Pada Karyawan KSPPS BMT NU Jawa Timur Di Kec. Gapura Kabupaten Sumenep) - Nabila Aulia; M. Isa Anshori (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
This study has an objective to determine the effect of motivation on employee performance through creative behavior of leader as an intervening variable on employees of KSPPS BMT NU East Java, Gapura Sub District. In this study, the writer uses a probability sampling method that is a sampling to provide equal opportunities for each member of the population to be selected as a member of the sample, with a simple random sampling technique by taking samples from members of the population and doing it randomly with a consideration of at least 1 year of work with a population of 219 and a sample of 141 respondents. The methods used are questionnaires and interviews. The results of the study show that there is a partial effect of motivation and creative behavior of leader on employee performance and there is an effect of motivation on employee performance through creative behavior of leader as an intervening variable. The implication is that the main director as a leader in KSPPS BMT NU East Java can maintain and increase the motivation of the employee in order to improve employee performance.